A new species of Euphranta Loew (Diptera: Tephritidae: Trypetinae: Adramini) from India - David, K.j.; Hancock, D.l.; Sankararaman, H.; Sachin, K.; Sudhir, Singh (Zootaxa, 2020)
A new species of Euphranta Loew, E. siruvani David, Hancock & Sankararaman, sp. n. is described from India. Postabdominal structures of E. hyalipennis David & Freidberg and E. haldwanica Hancock & Goodger are illustrated and described. A revised key to Euphranta from India is also provided.